Evaluasi atau Penilaian Pembelajaran bagi Anak Berkebutuhan Khusus (Tuna Rungu) - Baniaturrohmah, Fitri; Abdullah, Abid; Mayangkoro, Andhika Surya; Djaka, Cahya Tri; Husna, Difa’ul (MASALIQ, 2023)
Evaluation or assessment of learning for children with special disabilities, especially the deaf, is a problem that must be solved or resolved in order to support the success of inclusive education itself. Evaluation of learning can be defined as the process of obtaining data and information needed to determine how far and how learning has taken place so that assessments and improvements can be carried out to maximize results. Learning evaluation has a useful purpose for determining the level of eligibility and/or quality and accreditation of the inclusive education. In conducting this research, the writer uses a qualitative approach, because a qualitative approach is easier to use, flexible, and relevant to these problems.